2023
DOI: 10.1097/yco.0000000000000829
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the gut microbiome and mood disorders

Abstract: Purpose of reviewThe gut microbiome is in constant bidirectional communication with the brain through the microbiota-gutbrain-axis. Mood disorders are among the most common psychiatric disorders and include major depressive disorder and bipolar disorder. The gut microbiome is altered in individuals with mood disorders and has a role in its inflammatory pathophysiology. In this article, we performed a narrative review of clinical studies, randomized controlled trials and meta-analyses addressing advances in gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In addition, there was diversity in the healthy human gut microbiota [34]. However, travel promotes or rushes the process of gut microbial fluctuation, and travel can contribute to the global spread of antimicrobial resistance and diarrhea [14,35,36]. One interesting finding was that although all travelers did not experience diarrhea, a higher risk of gut microbial alteration was found in travelers than non-travelers in our study.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…In addition, there was diversity in the healthy human gut microbiota [34]. However, travel promotes or rushes the process of gut microbial fluctuation, and travel can contribute to the global spread of antimicrobial resistance and diarrhea [14,35,36]. One interesting finding was that although all travelers did not experience diarrhea, a higher risk of gut microbial alteration was found in travelers than non-travelers in our study.…”
Section: Discussionmentioning
confidence: 49%
“…However, no significantly correlative known external factors were found in this study. Travelers were contacting an altered environment, with many covariates that caused this promotion of microbial fluctuation, such as mood [35], diet [36] and so on. The factors that led to gut microbial disorder were complex and ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Though research is limited, Martins et al [62], highlight that the findings of observational studies suggest that a high-quality diet, characterized as high in fruits, vegetables, legumes, nuts, whole grains and high-quality protein sources, have a counteractive effect on mood disorders, particularly major depressive disorder and bipolar disorder. A recent review reported more specific findings, noting that although more clinical trials are needed, probiotic supplementation seemed to be a positive add-on therapy for major depressive disorder treatment [63]. Research into specific nutrients and their mechanisms of action in this area is still a relatively new area with much work remaining until definitive recommendations can be established.…”
Section: The Possible Role Of Nutrition In Recovery From Mtbimentioning
confidence: 99%
“…From the clinical perspective of depression, on the one hand, patients present symptoms including low mood, insomnia and fatigue, on the other hand, the immune system, nervous system and endocrine system of the patients are affected as well, which further results in the changes of endogenous substances [21–23] . Metabolomics can analyze and compare the changes of metabolites in the body under different pathophysiological states, and search for the relative relationship of pathophysiological changes and characteristic biomarkers through quantitative analysis of metabolites [24–27] . Additionally, recent studies have found that intestinal flora is closely related to the occurrence and development of depression, and intestinal flora affects the metabolic phenotype of the host and participates in the co‐metabolic process of the host.…”
Section: Introductionmentioning
confidence: 99%